Neoadjuvant cryotherapy improves dysphagia and may impact remission rates in advanced esophageal cancer - Shah, Tilak; Kushnir, Vladimir; Mutha, Pritesh; Majhail, Mankanchan; Patel, Bhaumik; Schutzer, Matthew; Mogahanaki, Drew; Smallfield, George; Patel, Milan; Zfass, Alvin (Endoscopy International Open, 2019)
Background and study aims Liquid nitrogen spray cryotherapy (LNSC) can provide rapid dysphagia relief, and is postulated to stimulate a local antitumor immune response. The aim of this prospective pilot clinical trial was to evaluate the safety and efficacy of LNSC when administered prior to chemoradiotherapy.Patients and methods Treatment-naïve adult patients with dysphagia at the time of biopsy-proven squamous carcinoma or adenocarcinoma of the esophagus were prospectively enrolled at two tertiary medical centers. Patients underwent a single session of LNSC. The primary outcome measure was change in dysphagia at 1 and 2 weeks post-cryotherapy. A secondary outcome measure was clinical complete response rate (CR) following chemoradiotherapy.Results Twenty-five patients were screened, of whom 21 patients were eligible and enrolled. There were seven with metastatic and 14 with locally advanced cancer. The primary outcome of dysphagia improvement of ≥ 1 point occurred in 15/21 patients (71 %) at 1 week, and 10/20 patients (50 %) at 2 weeks. The median dysphagia score improved by 1 at 1 week (P = 0.0003), and 0.5 at 2 weeks (P = 0.02). Six of nine patients (67 %) with locally advanced cancer who completed chemoradiation did not have residual tumor cells on mucosal biopsy, and five of nine patients (56 %) had a clinical CR. There were no serious cryotherapy-related complications.Conclusions LNSC provided safe and effective palliation for esophageal cancer patients who presented with dysphagia at index diagnosis. Its combination with chemoradiotherapy did not lead to any serious toxicity. Our study provides a scientific rationale for pursuing larger clinical trials addressing synergistic effects of combining LNSC with chemoradiation.